(untitled) (Research, Society and Development, 2021)
The demand for healthier foods, produced locally, with characteristics of local culture, which guarantee social justice, has popularized the Short Food Chains. These networks have proven to be a reliable substitute for conventional supply chains. In addition, it enables the socioeconomic empowerment of the family farmer, ensuring more stable revenues. The present study aimed to analyze the development of a short chain through a local distribution network of organic baskets, a family farm property. The results showed a growth of more than 400% in production and an increase of 1,500% in the sales price of the baskets in the period 2016/2019, from the development and consolidation of the short chain, here called "Agroecological Family Short Chain".